Corporate Responsibility in the Crime of Money Laundering in Indonesia - Nia Mudjiyanto; Didik Suhariyanto; G. Nyoman Tio Rae (Syntax Idea)
The crime of money laundering has a direct or indirect negative effect on the country's economy, as a negative effect on the effective use of resources and finances. TPPU issues are not only related to legal and law enforcement issues, but are also directly related to and affect national financial and economic issues, including national investment issues. The method used in this research is normative legal research which is carried out as an effort to obtain the necessary data regarding the problem. The data used is secondary data consisting of primary legal material, secondary legal material and tertiary legal material. Besides that, primary data is also used as supporting secondary data. Data analysis was carried out using qualitative juridical analysis methods. The research results obtained are that TPPU practices involve a lot of resources and funds that are used for illegal activities and can be detrimental to society, and a lot of funds cannot be used optimally. Proceeds of crime are usually invested in countries where money laundering appears safe, although returns are lower. The proceeds of this crime can be transferred from countries with good economies to countries with poor economies. Because it has a negative impact on financial markets and weakens citizens' trust in the international financial system.